Oversharing in the Digital Age According to Herbert Marcuse's Study - Reyza, Fadilla (Talenta Publisher, 2025)
This research focuses on discussing oversharing behavior from the perspective of a critical study of Herbert Marcuse's thinking, namely one-dimensional human theory. The research method used was a literature study, by collecting data related to Herbert Marcuse's thoughts and oversharing behavior. The research results showed that oversharing behavior is by the characteristics of a one-dimensional society mentioned by Herbert Marcuse, namely that; First, society is under the power of technological principles with the many choices of social media which have become a forum for oversharing. Second, modern society has become irrational as a whole, due to the unity between productivity and destructiveness, oversharing behavior subconsciously requires spending time checking what has been posted on social media.